2012
DOI: 10.1088/0264-9381/30/2/025006
|View full text |Cite
|
Sign up to set email alerts
|

A uniform treatment of the orbital effects due to a violation of the strong equivalence principle in the gravitational Stark-like limit

Abstract: We consider a binary system made of self-gravitating bodies embedded in a constant and uniform external field g. We analytically work out several orbital effects induced by a putative violation of the Strong Equivalence Principle (SEP) due to g. In our calculation, we do not assume e ∼ 0, where e is the binary’s orbit eccentricity. Moreover, we do not a priori choose any specific preferred spatial orientation for the fixed direction of g. Our results do not depend on any particular SEP-violating theoretical sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…So far, this has been a motivator for astrophysical and cosmological studies beyond GR without including dark energy or dark matter, as it is used for explaining the present accelerating and expanding universe and other interesting problems in galaxies such as missing mass. It is well known that there is a highly significant indication that the temporal or spatial variations of physics constants reported have orbital effects [9,10]. Evidence for these effects motivates us to interpret other data in terms of spatial variation.…”
Section: Introductionmentioning
confidence: 93%
“…So far, this has been a motivator for astrophysical and cosmological studies beyond GR without including dark energy or dark matter, as it is used for explaining the present accelerating and expanding universe and other interesting problems in galaxies such as missing mass. It is well known that there is a highly significant indication that the temporal or spatial variations of physics constants reported have orbital effects [9,10]. Evidence for these effects motivates us to interpret other data in terms of spatial variation.…”
Section: Introductionmentioning
confidence: 93%
“…It is also used to explain the accelerating expansion of our Universe at present and the missing-mass problem in galaxies. One of the most significant studies indicated the orbital effects of spatial variations of fundamental couplings [ 12 , 13 ]. Furthermore, these effects would also provide us a motivation to evaluate other observational data in order to determine such variations more accurately.…”
Section: Introductionmentioning
confidence: 99%